2016
DOI: 10.21037/tau.2016.08.02
|View full text |Cite
|
Sign up to set email alerts
|

Urethral catheters and medical malpractice: a legal database review from 1965 to 2015

Abstract: BackgroundUrethral catheters (UCs) are commonly used in medicine and are associated with complications such as urinary tract infections (UTIs) and trauma. Given UC complications and their ubiquitous usage in healthcare, there is a potential for liability risk. We aim to explore litigation involving UC-related complications.MethodsThe LexisNexis legal database was queried for all state and federal cases from January 1965 through October 2015 using the terms “urethral catheter” or “Foley catheter” in combination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 28 publications
0
8
1
Order By: Relevance
“… 7 Using administrative data on surgical procedures, Aaronson et al 8 concluded that catheter-associated complications were reported rarely but were significantly associated with increased length of hospital stay and catheter-associated urinary tract infection rates. Awad and colleagues 15 conducted a legal database review of the association of urethral catheters with medical malpractice from 1965 to 2015 and reported that the most common malpractice claim was traumatic insertion of a urethral catheter (48% of claims). These investigators noted that several of the lawsuits involved a spouse who claimed loss of consortium (deprivation of the benefits of a family relationship because of injuries caused by the tort).…”
Section: Discussionmentioning
confidence: 99%
“… 7 Using administrative data on surgical procedures, Aaronson et al 8 concluded that catheter-associated complications were reported rarely but were significantly associated with increased length of hospital stay and catheter-associated urinary tract infection rates. Awad and colleagues 15 conducted a legal database review of the association of urethral catheters with medical malpractice from 1965 to 2015 and reported that the most common malpractice claim was traumatic insertion of a urethral catheter (48% of claims). These investigators noted that several of the lawsuits involved a spouse who claimed loss of consortium (deprivation of the benefits of a family relationship because of injuries caused by the tort).…”
Section: Discussionmentioning
confidence: 99%
“…These also affect the attitude of care, such as defensive medicine, overtreatment, etc. [ 10 11 ]. Therefore, further research on aspects of prevention of medical litigation should be conducted.…”
Section: Discussionmentioning
confidence: 99%
“…These costs did not include management of long-term complications such as urethral stricture disease. In addition, UCI is the commonest catheter-related malpractice claim [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…This yields a total healthcare burden in the US of $2 billion dollars per year. These costs are exclusive of managing long-term complications of urethral strictures or any potential medico-legal costs [ 7 ].…”
Section: Introductionmentioning
confidence: 99%